Preparation of Co-Amorphous Systems by Freeze-Drying - Melvin Wostry; Hanna Plappert; Holger Grohganz (MDPI AG, 2020)
Freeze-drying was evaluated as a production technique for co-amorphous systems of a poorly water-soluble drug. Naproxen was freeze-dried together with arginine and lysine as co-former. To increase the solubility of naproxen in the starting solution, the applicability of five surfactants was investigated, namely sodium dodecyl sulfate, pluronic F-127, polyoxyethylene (40) stearate, tween 20 and TPGS 1000. The influence of the surfactant type, surfactant concentration and total solid content to be freeze-dried on the solid state of the sample was investigated. X-ray powder diffraction and differential scanning calorimetry showed that the majority of systems formed co-amorphous one-phase systems. However, at higher surfactant concentrations, and depending on the surfactant type, surfactant reflections were observed in the XRPD analysis upon production. Crystallization of both naproxen and amino acid occurred from some combinations under storage. In conclusion, freeze-drying was shown to be a feasible technique for the production of a selection of co-amorphous drug-amino acid formulations.